LAPTM4B allele *2 is a marker of poor prognosis for gallbladder carcinoma. - Guojun Zhai; Kaowen Yan; Xiaoxu Ji; Wenrui Xu; Jiuling Yang; Fuxia Xiong; Jing Su; Michael A McNutt; Hua Yang (PLoS ONE, 2012)
BACKGROUND: Lysosomal protein transmembrane 4 beta (LAPTM4B) is a novel cancer-related gene which has two alleles designated LAPTM4B*1 and LAPTM4B*2. In this study we investigated the correlation of LAPTM4B genotype with prognosis and clinicopathologic features in patients who had undergone curative resection for gallbladder carcinoma (GBC). METHODOLOGY/PRINCIPAL FINDINGS: PCR assay was performed to determine the LAPTM4B genotype in 85 patients. The correlation of LAPTM4B genotype with clinicopathologic parameters was assessed with the Chi-squared test. Differences in patient survival were determined by the Kaplan-Meier method. Multivariate analysis of prognostic factors was carried out with Cox regression analysis. Patients with LAPTM4B *2 had both significantly shorter overall survival (OS) and shorter disease-free survival (DFS) (both P<0.001). Multivariate analysis showed that LAPTM4B genotype is a prognostic factor for OS and DFS (both P<0.001). CONCLUSIONS/SIGNIFICANCE: LAPTM4B allele *2 is a risk factor associated with poor prognosis in patients with resected GBC, and LAPTM4B status may be therefore be useful preoperatively as an adjunct in evaluation of the operability of GBC.